Sentence Structure of Twitter Messages - Klika, Lukáš (Univerzita Pardubice, 2017)
This bachelor thesis focuses on the usage of ellipsis in twitter messages by native and non-native speakers of English. The paper presents ellipsis, its categories and criteria. It also introduces the terms of recoverability and position of ellipsis. Additionally, it covers the clausal elements which are commonly ellipted. The analysis of twitter messages focuses on the frequency of ellipsis in tweets of both native and non-native speakers of English in order to find differences in the usage of ellipsis.
Struktura vět twitterových zpráv
Keywords: elipsa; twitter; redukce; návratnost; situační návratnost; strukturální návratnost; anaforická návratnost; kataforická návratnost; ellipsis; twitter; reduction; recoverability; situational recoverability; structural recoverability; anaphoric recoverability; cataphoric recoverability